BOND CONNECTIONS OF HIGH PERFORMANCE CONCRETE (HPC) AND STEEL: "EXPERIMENTAL VERIFICATION OF SELECTION GLUED FOR TWO DIFFERENT SURFACES OF STEEL" - Tomáš Blažek; Jakub Řepka; Tomáš Vlach (Acta Polytechnica CTU Proceedings)
This article deals with the test of selected adhesives for glued connection of high performance concrete and steel plates with various surface treatments. Results of this experiment can be used as a basis for the possible anchoring of concrete facade elements to the steel grate, the possible bonding of steel anchors on the surface of concrete facade elements. High performance concrete is a concrete that exceeds the compressive strength 100 MPa after 28 days. The second adherent is the uncoated steel and the steel with zinc coating as a second variant. Samples were tested in two different ways. The first experiment verified the single tensile strength of bond connection. The second test verified the shear strength, which is very important for connection designing.